2021
DOI: 10.1007/s11136-021-02951-w
|View full text |Cite
|
Sign up to set email alerts
|

The impact of multimorbidity patterns on health-related quality of life in the general population: results of the Belgian Health Interview Survey

Abstract: Background Chronic diseases and multimorbidity are a major cause of disease burden—for patients, caregivers, and society. Little is known however about potential interaction effects between specific disease combinations. Besides an additive effect, the presence of multiple conditions could also act synergistically or antagonistically regarding the impact on patients’ health-related quality of life (HRQoL). The aim was to estimate the impact of coexisting chronic diseases on HRQoL of the adult gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 61 publications
2
17
1
Order By: Relevance
“…In our study we had n=178 (49%) males and n=184(51%) females. This was similar to earlier studies related to multimorbidity and quality of life conducted in Japan (15) and Belgium (5 ). Our sample mean for education was 12.07+/-4.2.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study we had n=178 (49%) males and n=184(51%) females. This was similar to earlier studies related to multimorbidity and quality of life conducted in Japan (15) and Belgium (5 ). Our sample mean for education was 12.07+/-4.2.…”
Section: Discussionsupporting
confidence: 91%
“…(3) Pakistan is facing a similar demographic transition as in other Asian counterparts residing in the region. (4) With this increase in the ageing populations there is an increase in ailments (5) It is evident in the current demographics data from developed as well as the underdeveloped and developing nations, that the ageing population is gripped under an array of illnesses that may hinder in the way of their daily activities, may completely leave them immobile or cause more inconvenience through these multiple co morbidities. (6) Multimorbidity and quality of life have been shown by studies to have inverse relationship.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, individuals who reported habitually taking medication obtained lower scores in the perception of HRQoL. Chronic disease conditions are a risk factor for a negative perception of QoL, 9,10,22,23 and this was the dependent variable with the highest predictive value. The literature has shown that this situation occurs mainly regarding the variables related to physical health and when we are in the presence of some specific conditions, including hypertension, diabetes, lower back pain, knee osteoarthritis, stroke and mental disorders or when there is multimorbidity.…”
Section: Quality Of Life and Health Variablesmentioning
confidence: 90%
“…The literature has shown that this situation occurs mainly regarding the variables related to physical health and when we are in the presence of some specific conditions, including hypertension, diabetes, lower back pain, knee osteoarthritis, stroke and mental disorders or when there is multimorbidity. 9,[23][24][25] It seems important to emphasize the fact that the presence of chronic disease does not seem to inhibit individuals from practicing PA.…”
Section: Quality Of Life and Health Variablesmentioning
confidence: 99%
“…The management of multimorbidity is challenging given that most guidelines and research are still targeted at single diseases. As a result, the negative impact of multimorbidity is often greater than the additive effects of individual diseases [6].…”
Section: Introductionmentioning
confidence: 99%